Peningkatan Kapasitas Siswa Smk dalam Strategi Pemasaran dan Branding Melalui Digital Marketing Di Era Ekonomi Kreatif [Enhancing Vocational High School Students' Capacity in Marketing and Branding Strategies Through Digital Marketing in the Era of Creative Economy] - Aprilia, Sherly; Jannah, Roudlotul; Arifyanto, Dita Narfadilah; Nurum, Mukafi; Aulia, Rohmatul (Indonesia Berdaya, 2025)
Abstract. This community service program aims to enhance the entrepreneurial competence of vocational high school students, particularly in the creative industry, through the implementation of integrated marketing strategy training. The program was conducted at SMK Al-Islah Surabaya with a specialization in Visual Communication Design (DKV), as an effort to bridge the gap between technical design skills and the understanding of strategic marketing aspects. The implementation method included needs observation, material planning, a three-day interactive training, and evaluation. The materials provided included Entrepreneurship and Value Proposition, 5A Analysis, and Practice. The evaluation results indicate a significant improvement in students' understanding of marketing concepts, increased active participation in practical sessions, and the formation of an entrepreneurial mindset and an attitude of professionalism. This program demonstrates that an applicative, educational-participatory approach is effective in enhancing the readiness of vocational high school students for the workforce and encouraging early innovation in the creative industry sector. Abstrak. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi kewirausahaan siswa SMK, khususnya pada bidang industri kreatif, melalui implementasi pelatihan strategi pemasaran terpadu. Program ini dilaksanakan di SMK Al-Islah Surabaya dengan konsentrasi keahlian Desain Komunikasi Visual (DKV), sebagai upaya menjembatani kesenjangan antara keterampilan teknis desain dengan pemahaman aspek pemasaran strategis. Metode pelaksanaan meliputi observasi kebutuhan, perencanaan materi, pelatihan interaktif selama tiga hari, serta evaluasi. Materi yang diberikan mencakup Dasar Kewirausahaan dan Value Proposition, Analisis 5A, dan Praktik. Hasil evaluasi menunjukkan peningkatan signifikan pemahaman siswa terhadap konsep pemasaran, peningkatan keterlibatan aktif dalam praktik, dan terbentuknya pola pikir kewirausahaan serta sikap profesionalisme. Program ini membuktikan bahwa pendekatan edukatifpartisipatif yang aplikatif efektif meningkatkan kesiapan siswa SMK dalam menghadapi dunia kerja dan mendorong inovasi sejak dini di sektor industri kreatif.